INSTITUTION OF HOMES FOR THE AGED: NURSE'S ROL - Elisiane Lorenzini; Neli Dias Monteiro; Karen Bazzo (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927169 Objective: aimed at getting acquainted with Brazilian scientific productions that discuss the nurse's role of Homes for the Aged. Method: it is an integrative review carried out from the database and virtual library, through the descriptors: nursing, elderly, Homes for the Aged, published between 2006 and 2012. Results: the sample of this study consists of articles from several nursing journals. The largest number of articles on this topic was found in the Scientific Electronic Library Online. Conclusions: it was possible to conclude that the nurse's role in such institutions is highly important for the execution of actions centered in the promotion of quality of life and of health literacy. The challenge of providing qualified nursing assistance and care for the elderly remains.